Politics, Intelligence and Elections in Late Colonial India: Congress and the Raj in 1937 - Muldoon, Andrew (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2009)
This article addresses questions of political reform and colonial intelligence collection in 1930s India. It focuses on the expectations British colonial officials had of the impact of the 1935 Government of India Act reforms on Indian political behaviour, especially regarding the creation of largely autonomous provincial assemblies. The 1937 provincial elections put these colonial suppositions to the test, and found them wanting. The article outlines the flawed and blinkered nature of colonial information gathering, demonstrating how the election results, particularly the very strong showing by an organized Indian National Congress, came as a real surprise to colonial administrators. However, the article also shows that these results did not necessarily change colonial opinions about Indian politics overmuch, as administrators and governors sought to frame what had happened within their existing understanding of India. Overall, this piece argues for the persistence of certain ways of colonial thinking in India, driven by ideological or cultural biases, as well as by the real limitations on the capability of the colonial state.